Forecasting Model of the Money Price of Any Technical Work During Construction Process in Any Time Instance Due to the Management of the Construction Contract as a Forward Commodity Contract - Metallinos Pavlos (Modelling in Civil Environmental Engineering, 2022)
The full expansion of the general formula, which calculates the money price of a forward contract at the end of the prearranged period T, makes us tangibly understand the relationship between time and money function {M(oney)=f [t(ime)]} in determining the purchase price/cost of a forward commodity. Similarly, in the case of the production process of construction, it has been shown that there is a time-money function {M(oney) = f [t(ime)]}, which determines the purchase price/cost of a technical commodity. The purpose of this paper is to introduce the possibility of studying and interpreting of the dynamic variations of the parameters that shape the final monetary exchange value of any construction as demonstrated by the time-money relationship and determined by research and financial management.